Spirituality of pedagogical communication – the basis of sustainable development of society - Babayev, Volodymyr; Pazynich, Stanislav (Національний технічний університет "Харківський політехнічний інститут", 2019)
The essence and content of the concept of “spiritual pedagogical communication” are considered and the reasons for the ineffectiveness of the latter with regards to the educational process and the nurturing of well-trained specialists of the new generation in relation to the needs of modern society are substantiated. The place and role of the teacher’s moral and aesthetic potentials in the process of the formation and development of student youth’s spiritual culture are outlined; the priorities and spiritual values of the modern teacher are analyzed.

Розглянуто сутність і зміст поняття «духовне педагогічне спілкування» та обґрунтовано причини недостатньої ефективності впливу його на процес освіти й виховання всебічно розвинутих фахівців нової генерації щодо потреб сучасного суспільства. Визначено місце і роль моральнісного й естетичного потенціалів педагога у процесі формування і розвитку духовної культури студентської молоді; проаналізовано пріоритети і духовні цінності сучасного педагога.
Духовність педагогічного спілкування – субоснова сталого розвитку суспільства
Keywords: personality; educational process; morality; особистість; навчально-виховний процес; моральність